Sebab-Sebab Terjadinya Perceraian Dan Dampaknya Terhadap Perempuan Di Aceh (Analisis Perbandingan Putusan Mahkamah Syar’iyah Meulaboh Aceh Barat dan Mahkamah Syar’iyah Jantho Aceh Besar Tahun 2019-2021) - Arifin Abdullah (Pusat Studi Wanita UIN Ar-Raniry, 2023)
Divorce is a problem that occurs between legal married couples caused by several problems that arise in the household that lead to divorce. The word cause became the beginning of the emergence of rift in the household, and became the starting point for various problems experienced by the married couple. Divorce is regulated in Article 39 No. 1 of 1974 concersing marriage, and Article 116 KHI, in Islamic law divorce is an act that is lawful but hated by Allah SWT as contained in the Hadith of the prophet Muhammad, and one of the words of Allah SWT contained in Q.S Al-Ahzab : 49. This discussion focuses on what are the most dominant causes of divorce at the Meulaboh Syar’iyah court and Jantho Syar’iyah court in 2019-2021. The problems rised are what are the causes of the divorce at the Meulaboh Syar’iyah court and the Jantho Syar’iyah court and what are the judges’ considerations in deciding divorce cases in 2019-2021. The research method used in this study is a comparative descriptive method with a comparative qualitative method approach. The results of this study indicate that the Meulaboh Syar'iyah Court and the Jantho Syar'iyah Court have sorted out several causes of divorce such as Continuous Disputes and Fighting, Leaving One Party, Sentenced to Prison, Domestic Violence, Economy, Disability, Apostasy, Drunkenness, Madat, Gambling, Polygamy, and Forced Marriage. Of all the reasons that have been mentioned, the most frequent divorces at the Meulaboh Syar'iyah Court and the Jantho Syar'iyah Court are due to Continual Disputes and Arguments, and have experienced increases and decreases from 2019-2020.